2010
DOI: 10.1007/s13181-010-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide’s Role in the Management of Sulfonylurea-Induced Hypoglycemia

Abstract: The objective is to evaluate the evidence regarding octreotide's efficacy as a treatment for sulfonylurea-induced hypoglycemia. A search of PubMed for articles published from 1965 to 2008 using combinations of the terms octreotide, antidote, sulfonylurea, overdose, poisoning, and toxicity was performed. References from identified articles were reviewed for additional sources. Animal studies, case reports, case series, and randomized controlled trials were evaluated. An animal model of sulfonylurea overdose dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…In HIPOS‐ER, the secretagogue‐based therapy represented the largest group (50.5%) of hospitalized patients, and was the strongest predictor for hospitalization (OR 5.71). These results were to be expected because hypoglycaemia triggered by secretagogues can be long‐lasting, more severe, and recurrent . The present results are consistent with recent data from other studies, including those on secretagogues …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In HIPOS‐ER, the secretagogue‐based therapy represented the largest group (50.5%) of hospitalized patients, and was the strongest predictor for hospitalization (OR 5.71). These results were to be expected because hypoglycaemia triggered by secretagogues can be long‐lasting, more severe, and recurrent . The present results are consistent with recent data from other studies, including those on secretagogues …”
Section: Discussionsupporting
confidence: 93%
“…These results were to be expected because hypoglycaemia triggered by secretagogues can be long-lasting, more severe, and recurrent. 13,20,24,32,33 The present results are consistent with recent data from other studies, including those on secretagogues. 12,13,15,24,29,34 Severe hypoglycaemia is a serious adverse event associated with consequences such as a higher risk of accidents and death.…”
Section: 2% When Combined With Insulin)supporting
confidence: 93%
“…In sulfonylurea-induced hypoglycemia, there is even a possibility that administered dextrose stimulates insulin secretion and prolongs hyperinsulinemia, resulting in recurrent hypoglycemia [1,2]. When patients are treated with incretin-based therapy, insulin secretion by the dextrose could be further enhanced, because of the glucose-dependent nature of incretin actions.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon relies on glycogen stores and has a short pharmacologic duration of glucagon. In addition to other animal and human data, one small prospective, doubleblind, placebo-controlled study found that one-time administration of octreotide in adult sulfonylurea poisonings increased serum glucose values for the first 8 h after administration and decreased the number of recurrent hypoglycemic episodes (14,15). Our regional poison control center routinely recommends octreotide 50-100 mg s.c. or i.v.…”
Section: Discussionmentioning
confidence: 99%